Pengaruh Human Relation Dan Lingkungan Kerja Terhadap Etos Kerja Karyawan Pada PT. Seafood Industrial Group (SIG) Asia Bitung - Hamisi, Yusuf; Karamoy, Tiffany S. (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
The purpose of this research is to find out how the influence of human relations variables and work environment variables partially and simultaneously on employee work ethic variables. This research is a type of descriptive research with a quantitative approach. Population is 230 production employees at PT. Seafood Industrial Group (GIS) Asia Bitung. Samples are 58 employees. Data analysis uses multiple linear regression. The results of research and discussion indicate that human relations or relations between humans and the work environment partially and overall have a significant impact on the work ethic of workers at PT . Seafood Industrial Group (SIG) Asia Bitung.